Immunocytokines in cancer immunotherapy: opportunities and challenges - Wang, Shubo; Yao, Lisha; Cai, Jianying; Gao, Huiquan; Zhou, Fuxin (Frontiers in Oncology, 2026)
The clinical use of cytokines is restricted by dose-limiting toxicities (DLT), short half-life, and rapid renal clearance, which collectively hinder administration at therapeutically effective doses. Cytokines fused to antibodies (antibody–cytokine fusion proteins, or immunocytokines) have emerged as a promising strategy to overcome these limitations by directing cytokine payloads to the tumor microenvironment, thereby enhancing antitumor immune responses while reducing off-target effects. Various antibody formats, including intact IgGs and IgG fragments, have been engineered to target tumor-associated cell-surface antigens or extracellular matrix (ECM) components, and fused to a wide range of cytokines. Preclinical studies consistently demonstrate enhanced antitumor efficacy and reduced systemic toxicity compared to unconjugated cytokines, with further synergistic effects observed when combined with chemotherapy, radiotherapy, or immune checkpoint inhibitors. Recent advances include anti-PD-1–based immunocytokines that selectively deliver cytokines to intratumoral CD8+ T cells, restoring their function and driving potent antitumor activity. Despite encouraging results, efficacy and safety concerns remain significant challenges for clinical application. Strategies such as cytokine engineering, prodrug approaches, and rational molecular design are being pursued to enhance therapeutic outcomes while minimizing side effects. This review summarizes the conceptual framework, structural design principles, preclinical and clinical progress, current limitations and potential strategies for future development of immunocytokines in cancer immunotherapy.